Cryptococcus gattii molecular type VGII as agent of meningitis in a healthy child in Rio de Janeiro, Brazil: report of an autochthonous case Cryptococcus gattii tipo molecular VGII como agente causador de meningoencefalite em criança saudável no Rio de Janeiro, Brasil: relato de um caso autóctone - Vitor Laerte Pinto Junior; Marcos Vinicius da Silva Pone; Sheila Moura Pone; João Maurício Scarpellini Campos; José Roberto Pereira Garrido; Ana Cláudia Mamede Wiering de Barros; Luciana Trilles; Gláucia Gonçalves Barbosa; Bernardina Penarrieta Morales; Cláudia de Carvalho Falci Bezerra; Márcia dos Santos Lazéra (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
Cryptococcus gattii causes meningoencephalitis in immunocompetent hosts, occurring endemically in some tropical and subtropical regions. Recently, this fungus was involved in an outbreak in Vancouver Island and British Columbia (Canada). In this temperate region, the VGII type is predominant. The paper describes an autochthonous case of meningoencephalitis by C. gattii VGII in a previously health child in Rio de Janeiro, considered nonendemic region of Brazil. The fungus was identified by biochemical tests and the molecular type was determined by URA5-RFLP. The present report highlights the need for clinical vigilance for primary cryptococcal meningitis in nonendemic areas. Cryptococcus gattii é causa de meningoencefalite em hospedeiros imunocompetentes, ocorrendo endemicamente em regiões tropicais e subtropicais. Recentemente foi causador de surtos na Ilha de Vancouver e na Columbia Britânica (Canadá). Nesta região de clima temperado, o tipo VGII é predominante. Relatamos um caso de meningoencefalite pelo C.gattii tipo VGII acometendo criança previamente saudável autóctone do Rio de Janeiro, região não endêmica do Brasil. O agente foi identificado por testes bioquímicos e o tipo molecular determinado através de URA5-RFLP. O presente relato enfatiza a necessidade de vigilância clínica para a meningite criptocóccica primária em áreas não endêmicas.